Sex Differences in PrEsentation, Risk Factors, Drug and Interventional Therapies, and OUtcomes of Elderly PatientS with Pulmonary Embolism: Rationale and design of the SERIOUS-PE study. Issue 214 (June 2022) - Bikdeli, Behnood; Piazza, Gregory; Jimenez, David; Muriel, Alfonso; Wang, Yun; Khairani, Candrika D.; Rosovsky, Rachel P.; Mehdipoor, Ghazaleh; O'Donoghue, Michelle L.; Spagnolo, Primavera; Dreyer, Rachel P.; Bertoletti, Laurent; et al.
Abstract: Background: Sex is an important factor associated with pulmonary embolism (PE) disease presentation and outcomes, which may be related to pathobiological, social, and treatment-based differences. We are seeking to illuminate sex differences in pulmonary embolism presentation, care, and outcomes using an international registry and a national US database of people 65 years and older, the age group in which the majority of these events occur. Methods: The Sex Differences in PrEsentation, Risk Factors, Drug and Interventional Therapies, and OUtcomes of Elderly PatientS with Pulmonary Embolism (SERIOUS-PE) study has been designed to address knowledge gaps in this area. This study will use data from the Registro I nformatizado E nfermedad T rombo E mbolica (RIETE) registry and the US Medicare Fee-For-Service beneficiaries. RIETE is a large international registry of patients with venous thromboembolism with data collected on PE presentation, risk factors, co-morbidities, drug and interventional therapies, as well as 30-day and 1-year outcomes (including recurrent VTE, major bleeding, and mortality). Data from US Medicare Fee-For-Service beneficiaries will be used to understand the sex differences in PE hospitalizations, advanced therapies, and outcomes at 30-day and 1-year follow-up. Assessment of outcomes in both databases will be performed in unadjusted models, as well as those adjusted for demographics, co-morbidities, and treatments, to understand whether the potential sex differences in outcomes are related to differences in risk factors and co-morbidities, potential disparities in treatment, or a plausible biological difference in women versus men. Linear trends will be assessed over time. Results: RIETE data from March 2001 through March 2021 include 33, 462 elderly patients with PE, of whom 19, 294 (57.7%) were women and 14, 168 (42.3%) were men. In the Medicare Fee-For-Service database, between January 2001 and December 31, 2019, 1, 030, 247 patients were hospitalized with a principal discharge diagnosis of PE, of whom 599, 816 (58.2%) were women and 430, 431 (41.8%) were men. Conclusions: Findings from the SERIOUS-PE study will help address important knowledge gaps related to sex differences in presentation and risk factors, treatment patterns, and outcomes of older adults with PE. The results may guide changes in prognostic prediction rules based on sex-specific findings, identify sex-based disparities in care delivery that should be addressed by quality improvement, or uncover potential differences in response to available therapies that warrant testing in dedicated randomized trials. Highlights: Sex and age may impact pulmonary embolism (PE) presentation and outcomes. Sex differences in PE presentation, treatment patterns, and outcomes remain unknown. The SERIOUS-PE study will use two large data sources to answer these knowledge gaps. Treatment disparities need quality improvement initiatives to mitigate disparities. Adjusted analyses of outcomes will indicate whether sex-specific RCTs are needed.